2004
DOI: 10.1682/jrrd.2011.03.0063
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer output and its association with energy expenditure in persons with multiple sclerosis

Abstract: Abstract-Limited data support the strong association between rates of accelerometer activity counts and energy expenditure during dynamic activity in persons with multiple sclerosis (MS). This study examined the association between rates of activity counts and energy expenditure during walking by using two models of accelerometers and generated cut-points representing moderate-to-vigorous physical activity (MVPA) in persons with MS. Participants were 43 persons with MS and 43 controls who undertook 5 min of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 11 publications
1
89
1
Order By: Relevance
“…12 All three measures have been validated in people with MS. 13 The GLTEQ includes three items that measure the frequencies of strenuous, moderate, and mild physical activity over a 7-day period. The frequencies (ie, times per week) of strenuous, moderate, and mild physical activity were multiplied by 9, 5, and 3 metabolic equivalents, respectively, and then were summed to a total score (0-119).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 All three measures have been validated in people with MS. 13 The GLTEQ includes three items that measure the frequencies of strenuous, moderate, and mild physical activity over a 7-day period. The frequencies (ie, times per week) of strenuous, moderate, and mild physical activity were multiplied by 9, 5, and 3 metabolic equivalents, respectively, and then were summed to a total score (0-119).…”
Section: Methodsmentioning
confidence: 99%
“…This accelerometer was worn on an elastic belt around the waist during the waking hours of a 7-day period. The accelerometer data were downloaded, processed into 1-minute epochs, and then scored for wear time and minutes per day spent in MVPA using validated cut-points for MS. 12 Only days with sufficient wear time (ie, ≥600 minutes) were included in the analyses, and we averaged the minutes per day of MVPA across 2 or more available valid days. 14 We generated a composite physical activity measure for this study by 1) transforming the scale scores for each measure into z scores (ie, comparable units) and then 2) averaging the z scores for each measure per time point.…”
Section: Methodsmentioning
confidence: 99%
“…One file represented daily accelerometer wear time and the other file represented time spent in light physical activity (LPA) (100-1722 counts/min). 34 LPA was examined based on previous research that demonstrated associations between LPA and physical function in older adults with MS. 13 Participants were given written and graphic instructions to wear the accelerometer on a provided belt around the waist over the nondominant hip during all waking hours of a 7-day period, except when swimming, bathing, or showering. Accelerometer wear time data were checked against participant recorded wear times from a log sheet, and participants Participants further completed the measures of cognitive function and self-efficacy, followed by measures of physical function.…”
Section: Physical Activitymentioning
confidence: 99%
“…This accelerometer is small (3.8 × 3.7 × 1.8 cm) and lightweight (40.2 g), is typically worn on the waist near the center of mass, and records activity counts per unit time or epoch. 21 It has a battery life of up to 15 days and a memory capacity of 1 Mb. 22,23 Study participants wore the device on an elastic band on the hip to capture measurements of PA at different intensities, energy expenditure, and steps taken.…”
mentioning
confidence: 99%